Metal-organic-framework-derived 3D crumpled carbon nanosheets with self-assembled CoxSy nanocatalysts as an interlayer for lithium-sulfur batteries - Seo, Seung-Deok; Choi, Changhoon; Park, Dongjoo; Lee, Dong-Yeop; Park, Sangbaek; Kim, Dong-Wan (ELSEVIER SCIENCE SA, 2020)
Two-dimensional (2D) nanosheets are promising interlayers for enhancing the electrical conductivity and hindering the lithium polysulfide (LPS) shuttling in lithium-sulfur batteries (LSB). However, their dense 2D nature limits the electrolyte infusion and lithium ion transport, thereby decreasing the rate performance. Herein, we demonstrate that three-dimensional (3D) crumpled carbon nanosheets (CCNSs) decorated with a few nanometers of cobalt heterostructures (CoxSy) that are based on a 2D zeolitic imidazolate framework can improve both the LPS adsorption as well as the ion conduction of LSB interlayer. The method is simple and scalable; the 3D composites are fabricated by post-annealing of 2D metal organic frameworks, which are synthesized by a solution process at room temperature without surfactant. Interestingly, the assembly and polarity of cobalt heterostructures can be further manipulated by the annealing condition; this provides a scientific evidence for the nanostructural and compositional combination of polar compounds. Consequently, CoS/Co9S8@CCNS exhibits the best performance with a discharge capacity of 911 mA h g(-1) at 0.2C after 100 cycles (150% more than commercial sulfur cell) and the long-term cyclability of 600 mA h g(-1) at 1C after 500 cycles. This is attributed to efficient charge transfer as well as effective LPS adsorption and effective catalytic conversion; further, this is achieved by the synergetic effects of well-distributed polar compounds comprising few nanometers in size and optimal polarity on a highly conductive N-doped carbon nanosheet.
Keywords: TRAPPING-DIFFUSION-CONVERSION; RATIONAL DESIGN; GRAPHENE OXIDE; PERFORMANCE; POLYSULFIDES; SEPARATOR; CATHODE; ZIF-67; HETEROSTRUCTURES; NANOPARTICLES